Energetic Analysis of Mixed-Flow Grain Dryers: A Case Study in Hungary - Ferenc Péter Speiser; Bence Nagy; Ting Pan (Chemical Engineering Transactions)
Convective grain drying powered by natural gas is a highly energy-intensive process with a substantial impact on the secure storage of harvested grain. By improving energy efficiency and reducing natural gas consumption, it is possible to decrease the operation's ecological footprint by lowering CO2 emissions. However, previous studies often analyse the drying process as a whole, giving less attention to individual processes. For instance, uneven drying can lead to issues during storage, such as microbial growth and dust accumulation. This paper presents an energetic analysis of mixed-flow grain dryers based on a case study in Hungary for the long term. It examines the fundamental physical characteristics of each dryer and identifies key modifications to ensure proper operation. The paper also introduces a precision drying method that allows fine-tuning of process parameters (e.g., airflow, grain flow) to optimise grain moisture content to the desired level based on large-scale continuous temperature measurements. These measurements can also validate previous modifications, enabling ongoing monitoring of optimal operating conditions via heatmaps.